2012
DOI: 10.1123/ijspp.7.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Training Distribution, Physiological Profile, and Performance for a Male International 1500-m Runner

Abstract: This case study observed the training delivered by a 1500-m runner and the physiological and performance change during a 2-y period. A male international 1500-m runner (personal best 3:38.9 min:s, age 26 y, height 1.86 m, body mass 76 kg) completed 6 laboratory tests and 14 monitored training sessions, during 2 training years. Training distribution and volume was ascertained from training diary and spot-check monitoring of heart rate and accelerometry measurements. Testing and training information were discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 6 publications
5
67
0
2
Order By: Relevance
“…In addition, the improvements in performance in the cyclists after the 1-week taper differed across groups, thus demonstrating that the group responses to the overload week and tapering were not comparable, and pooling of the data may have masked important individual differences. In the elite athlete setting, training programmes, nutritional and medical interventions and monitoring programmes are individualised to the elite athlete in order to optimise outcome [149][150][151][152][153]. In summary, ARH may occur in response to training taper, with marked interindividual variation, which maybe attenuated in athletes with a higher training status; however, no studies exist in elite athletes.…”
Section: Evidence For Arh Following a Training Tapermentioning
confidence: 96%
“…In addition, the improvements in performance in the cyclists after the 1-week taper differed across groups, thus demonstrating that the group responses to the overload week and tapering were not comparable, and pooling of the data may have masked important individual differences. In the elite athlete setting, training programmes, nutritional and medical interventions and monitoring programmes are individualised to the elite athlete in order to optimise outcome [149][150][151][152][153]. In summary, ARH may occur in response to training taper, with marked interindividual variation, which maybe attenuated in athletes with a higher training status; however, no studies exist in elite athletes.…”
Section: Evidence For Arh Following a Training Tapermentioning
confidence: 96%
“…However, other studies (33,57,58) have observed increased PPO and mean power sustainable during a 40-km time trial (40-km TT) when high-intensity interval work (zone 3 training) is incorporated into the schedules of already well-trained cyclists; i.e., when the cyclists adopted a more polarized training-intensity distribution. In addition, the change of intensity distribution toward a more polarized model has been shown to improve maximal oxygen consumption, running economy, and running performance in a case study of an international 1,500-m runner (27). Indeed, the powerful stimulus afforded by short-term, high-intensity interval work for promoting metabolic and performance adaptations has also been demonstrated in studies on trained-cyclist (51), healthy-active (52), and sedentary (23) men and women.…”
mentioning
confidence: 91%
“…In recent years many studies have suggested that training intensity distribution plays a key role on endurance training adaptation not only in elite (Seiler and Kjerland, 2006;Seiler et al, 2007;Laursen, 2010;Seiler, 2010;Ingham et al, 2012), but also in well-trained recreational athlete (Esteve-Lanao et al, 2005, 2007Neal et al, 2013;Muñoz et al, 2014;Stöggl and Sperlich, 2014).…”
Section: Introductionmentioning
confidence: 99%